2017
DOI: 10.1039/c6ob02552h
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic ring-opening reactions of trans-2-aroyl-3-aryl-cyclopropane-1,1-dicarboxylates with hydrazines

Abstract: trans-2-Aroyl-3-aryl-cyclopropane-1,1-dicarboxylates when treated with arylhydrazines in refluxing EtOH gave dihydropyrazoles, whereas with hydrazines in refluxing AcOH, they formed cyclopropane-fused pyridazinones. Although in both cases the corresponding hydrazones are formed initially, the former case involves a subsequent 5-exo-tet nucleophilic ring-opening, and the later, a 6-exo-trig nucleophilic attack by the other hydrazone nitrogen. The products are obtained in moderate to excellent yields with comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Srinivasan and co-workers reported in 2017 the nucleophilic ring opening of trans -2-aroyl-3-arylcyclopropane-1,1-dicarboxylates with arylhydrazine to give dihydropyrazoles and cyclopropane-fused pyridazinones. 28a In 2021, they also observed that trans -2-aroyl-3-arylcyclopropane-1,1-dicarboxylate underwent ring-opening in the presence of naphthylamines and Sc(OTf) 3 to yield dibenzo[ c , h ]acridines. 28b…”
Section: Synthesis Of Nitrogen Heterocyclesmentioning
confidence: 99%
“…Srinivasan and co-workers reported in 2017 the nucleophilic ring opening of trans -2-aroyl-3-arylcyclopropane-1,1-dicarboxylates with arylhydrazine to give dihydropyrazoles and cyclopropane-fused pyridazinones. 28a In 2021, they also observed that trans -2-aroyl-3-arylcyclopropane-1,1-dicarboxylate underwent ring-opening in the presence of naphthylamines and Sc(OTf) 3 to yield dibenzo[ c , h ]acridines. 28b…”
Section: Synthesis Of Nitrogen Heterocyclesmentioning
confidence: 99%
“…reported the reaction of trans ‐2‐aroyl‐3‐arylcyclopropane‐1,1‐dicarboxylate 105 with arylhydrazines in refluxing EtOH for the synthesis of dihydropyrazole derivatives 106 in moderate to excellent yields. On reactions with hydrazine in refluxing AcOH, the authors obtained the cyclopropane‐fused pyridazinone derivatives 107 (Scheme ) . These reactions showed compatibility with a variety of substituted hydrazine and DACs.…”
Section: Synthesis Of Six‐membered Nitrogen Heterocyclesmentioning
confidence: 99%
“…135 Hence, pyrazolines 161 were produced in high yields. At the same time, the reaction of 160a with an unsubstituted hydrazine immediately yielded pyrazole 157a.…”
Section: Short Review Syn Thesismentioning
confidence: 99%